2021
DOI: 10.1021/acsnano.1c02486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internal Architecture on the Assembly of Soft Particles at Fluid Interfaces

Abstract: Monolayers of soft colloidal particles confined at fluid interfaces are at the core of a broad range of technological processes, from the stabilization of responsive foams and emulsions to advanced lithographic techniques. However, establishing a fundamental relation between their internal architecture, which is controlled during synthesis, and their structural and mechanical properties upon interfacial confinement remains an elusive task. To address this open issue, which defines the monolayer’s properties, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 57 publications
(166 reference statements)
6
78
0
Order By: Relevance
“…Vialetto et al [ 21 ] demonstrated that the control of the microgel structure during the synthesis process is a very interesting strategy for modulating the properties of the monolayers at fluid interfaces, providing a link between the particle conformation and the material properties. At small values of the interfacial density, it emerges that a mechanical response governed by the polymer corona formed within the interfacial plane by the most external chains, with the specific characteristics of the internal core playing a negligible role.…”
Section: Response Of Microgel Layers To Mechanical Perturbationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vialetto et al [ 21 ] demonstrated that the control of the microgel structure during the synthesis process is a very interesting strategy for modulating the properties of the monolayers at fluid interfaces, providing a link between the particle conformation and the material properties. At small values of the interfacial density, it emerges that a mechanical response governed by the polymer corona formed within the interfacial plane by the most external chains, with the specific characteristics of the internal core playing a negligible role.…”
Section: Response Of Microgel Layers To Mechanical Perturbationsmentioning
confidence: 99%
“…Solvated microgel networks can be compressed upon adsorption to fluid interfaces, leading to the deformation of the particle shape, to adapt their conformation to the interface. These morphological changes also control the dynamic behavior and interfacial packing of microgels at the interface, which, in turn, dominate the interfacial tension and rheological properties of the microgel-laden interfaces [ 19 ], playing a very important role in emulsion and foam stabilization [ 20 , 21 ]. In particular, the stretching of soft particles observed when assembled at fluid interfaces provides a better stability of the interface than the adsorption of traditional hard colloids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interfacial phase behavior of such spherical microgels has been studied intensively showing the effect of size and hard cores to the spreading of spherical microgels at the interface and their response to an increase in surface pressure within the Langmuir-Pockels trough. [14][15][16][17][18][19][20][21][22][23][24][25][26] Only few studies investigate the interfacial behavior of particles with an anisotropic shape.…”
Section: Introductionmentioning
confidence: 99%
“…The major challenge now lies in synthesizing a system that actually meets these conditions. Although the characteristics of the shell may recall systems such as ultra-low-crosslinked [17] or hollow microgels [18], these do not represent suitable systems to reproduce this behavior due to the lack of a true internal core. Menath et al [1] propose to use a hard core-soft shell system with clearly separated length-scales, in order to satisfy the first requirement posed by Jagla.…”
mentioning
confidence: 99%